Does Surgical Hip Dislocation and Periacetabular Osteotomy Improve Pain in Patients With Perthes-like Deformities and Acetabular Dysplasia? - Clohisy, John C. (Clin Orthop Relat Res, 2015)
BACKGROUND: Patients with symptomatic residual Perthes-like deformities may present with a combination of structural abnormalities including a large aspheric femoral head, short and wide femoral neck, high greater trochanter, and acetabular dysplasia. Sometimes, the hip is further compromised by concurrent symptomatic femoroacetabular impingement (FAI) (proximal femoral deformities) and structural instability (acetabular dysplasia). QUESTIONS/PURPOSES: We therefore sought to characterize (1) the intraoperative findings; (2) radiographic correction; and (3) early patient-reported outcomes, complications, and failures of treating complex Perthes-like hip deformities with combined surgical dislocation and periacetabular osteotomy (PAO). METHODS: We performed 694 hip preservation procedures between November 2006 and August 2010. Of these, 46 had residual Perthes-like hip deformities, defined as proximal deformity consistent with residual Perthes and a history of Perthes disease or treatment of pediatric hip dysplasia. Of these, we report on 16 patients (16 hips) with residual Perthes-like hip deformities and associated acetabular dysplasia (structural instability, defined as radiographic evidence of acetabular dysplasia with intraoperative confirmation of instability). These 16 patients were treated with a combined surgical hip dislocation to comprehensively address intraarticular and extraarticular sources of FAI and PAO to address structural instability and were analyzed at a minimum 24-month followup (median, 40 months; range, 24–78 months). No patients in this series were lost to followup. Ten patients’ hips had previous surgical treatment, including six with previous osteotomy. Operative findings were extracted from standardized prospectively collected intraoperative data collection forms. Radiographic correction was evaluated with established methods (lateral center-edge angle, anterior center-edge angle, acetabular inclination, center-to-trochanter distance) and clinical outcomes were measured with the modified Harris hip score (mHHS) as well as by prospectively recorded data on patient complications and followup. RESULTS: Acetabular labrochondral abnormalities included labral hypertrophy in all hips and labral and/or articular cartilage lesions requiring treatment in 13 hips. Radiographic analysis demonstrated consistent radiographic correction. The median preoperative mHHS improved from 64 to 92 at a median followup of 40 months (p < 0.001). Fourteen patients (14 hips) had a good or excellent clinical result. Two patients (two hips) were classified as failures based on mHHS less than 70 (n = 1) or conversion to total hip arthroplasty (n = 1). CONCLUSIONS: Combined surgical hip dislocation and PAO provides major deformity correction in Perthes-like hip deformities with associated acetabular dysplasia. Early clinical results suggest this technique is safe and effective. Long-term studies are needed to determine if improved long-term outcomes are associated with comprehensive deformity correction. LEVEL OF EVIDENCE: Level IV, therapeutic study.